H7N9: a low pathogenic avian influenza A virus infecting humans - Liu, Jun (Curr Opin Virol, 2014)
Human infections by the newly reassorted avian influenza A (H7N9) virus were reported for the first time in early 2013, and the virus was confirmed to be a low pathogenic avian influenza virus in poultry. Because continuously reported cases have been increasing since the summer of 2013, this novel virus poses a potential threat to public health in China and is attracting broad attention worldwide. In this review, we summarize and discuss the characteristics of the H7N9 virus revealed by the recent timely studies from the perspectives of epidemiology, host preference, clinical manifestations, immunopathogenesis, drug resistance, vaccine development, and burden of disease. This knowledge about the novel avian-origin H7N9 virus will provide a useful reference for clinical interventions of human infections and help to rapidly pave the way to develop an efficient and safe vaccine.